Let's Talk it Out: The Effects of Calibration Meetings on Performance Ratings. Issue 3 (8th August 2019) - Speer, Andrew B.; Tenbrink, Andrew P.; Schwendeman, Michael G.
ABSTRACT: Despite their use in practice, calibration meetings of performance appraisal ratings have received little attention in the academic literature to date. The current paper addresses this gap by formally defining calibration meetings and by investigating the nature and impact of calibration meetings on performance ratings across two field studies. Results indicated that calibration meetings do occur in organizations. The nature and cadence of calibration meetings varied considerably, but managers generally perceived calibrations as attempts to improve rating quality. Calibration meetings were also associated with increases in perceived frame-of-reference, perceived accountability, and perceived total information to base ratings upon. Further, results showed that post-calibration ratings correlated more with other measures assessing the job performance domain than pre-calibration ratings.